Dramatic and Reversible Water‐Induced Stiffening Driven by Phase Separation within Polymer Gels - Ming, Xiaoqing; Yao, Le; Zhu, He; Zhang, Qi; Zhu, Shiping (Advanced functional materials, 2022)
Responsive polymer materials possessing variable mechanical properties have shown promising practical applications, whereas water has clear advantages among the triggers owing to its wide abundance, green characteristics, as well as mild conditions involved. However, ubiquitous water‐induced softening would prevent polymer materials from applications with high humidity or aqueous environment. Herein, an unprecedented polymer gel material is reported that exhibits a dramatic and reversible water‐induced stiffening base on phase separation, differing from traditional ones that are usually weakened upon hydration due to the plasticizing effect. The material shows a large stiffness change in Young's modulus (as much as 104 times), which is much larger than that induced by glass transition and comparable to that caused by crystallization‐melting process. The polymer materials are fabricated in a facile way by introducing an ionic liquid and a lithium salt into a poly(benzyl methacrylate) network. Moreover, the volume remains almost unchanged during the reversible soft–stiff transition. A universal approach of water‐induced stiffening is proposed and verified on various systems. As for demonstration, this material is used for humidity‐induced shape memory. This work offers an effective method for developing water‐induced stiffened material and will pave the way toward potential applications for water‐responsive polymer materials. An unprecedented polymer material with a dramatic and reversible water‐induced stiffening (stiffness increase as much as 104 times) is introduced based on phase separation, differing from traditional ones that are usually weakened upon hydration. A universal approach for water‐induced stiffening is proposed and verified on various systems. This work would pave the way for the design and development of water‐responsive polymer materials.